EFFECT OF DIGITAL STORYTELLING ON TEACHING NARRATIVE - Eka Dyah Puspita Sari; Mia Fitria Agustina (Universitas Pendidikan Indonesia, 2021)
Narrative as one of English text genres functions to entertain readers. Some students do not achieve the purpose of narrative when they make it. It may happen because they do not understand the main purpose of narrative and lack of information on what should be and not should be put in the text. To overcome the problem, narrative was taught in different way by utilizing the digital form, and it is known as digital storytelling. Digital storytelling is expected to help students write narrative better so they can achieve the main purpose of the text. The main concern of this research is to find out the effect of digital storytelling in teaching narrative. It applied case study method with qualitative approach in the analysis. The data was gathered from 45 students who worked as the subject of the research. The result showed that 40 students (88,89%) felt digital storytelling help them to understand narrative better. This result implies that digital storytelling is proven to be beneficial in teaching narrative